2008
DOI: 10.1002/elps.200800013
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive CE‐UV method with dynamic coating of silica‐fused capillaries for monitoring of nucleotide pyrophosphatase/phosphodiesterase reactions

Abstract: A new highly sensitive capillary electrophoresis (CE) method applying dynamic coating and on-line stacking for the monitoring of nucleotide pyrophosphatases/phosphodiesterases (NPPs) and the screening of inhibitors was developed. NPP1 and NPP3 are membrane glycoproteins that catalyze the hydrolysis nucleotides, e.g. convert adenosine 5'-triphosphate to adenosine 5'-monophosphate (AMP) and pyrophosphate. Enzymatic reactions were performed and directly subjected to CE analysis. Since the enzymatic activity was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 46 publications
0
42
0
1
Order By: Relevance
“…For example, Krylov and co-workers developed a CE method named injectmix-react-separate and quantitate for screening enzyme inhibitors [13]. Iqbal et al reported a highly sensitive CE method applying dynamic coating and on-line stacking for monitoring of nucleotide pyrophosphatases/phosphodiesterases and screening of inhibitors [14]. Kang's group developed an electrophoretically mediated microanalysis (EMMA) based CE method for screening hexokinase and acetylcholinesterase inhibitors [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…For example, Krylov and co-workers developed a CE method named injectmix-react-separate and quantitate for screening enzyme inhibitors [13]. Iqbal et al reported a highly sensitive CE method applying dynamic coating and on-line stacking for monitoring of nucleotide pyrophosphatases/phosphodiesterases and screening of inhibitors [14]. Kang's group developed an electrophoretically mediated microanalysis (EMMA) based CE method for screening hexokinase and acetylcholinesterase inhibitors [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…3.1.4.1, E.C. 3.6.1.8, and 3.6.1.9) represent a group of conserved eukaryotic proteins that are expressed both as transmembrane ecto-enzymes and as soluble proteins in body fluids [1,2]. Three members of the NPP family hydrolyze nucleotides, namely, NPP1 (PC-1), NPP2 (autotaxin), and NPP3 (B10, gp130 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…PAP and PAPS will be negatively charged in buffers of pH values between 2 and 10 (see Supplementary Figure S1). Dynamic coating with polybrene is a powerful and suitable CE technique for charged analytes [19,23,24], since the more negatively charged analytes will migrate faster toward the detection window than the less charged analytes (due to the addition of the cationic surfactant polybrene causing a reversal of the electroosmotic flow (EOF)). A 75 mM phosphate buffer of pH 8.0 containing 0.002% polybrene was selected as running buffer.…”
Section: Development and Optimization Of Ce Methods For Monitoring Cstmentioning
confidence: 99%
“…Our group has long-standing experience in the quantification of nucleotides by CE, and especially in enzyme assays involving the formation or transformation of nucleotides [15][16][17][18][19][20][21][22]. Thus we decided to quantify the nucleotide PAP which is formed from the co-substrate PAPS during the CST reaction.…”
Section: Development and Optimization Of Ce Methods For Monitoring Cstmentioning
confidence: 99%